2018
DOI: 10.1302/2046-3758.74.bjr-2017-0302.r1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and osteoporosis on bone marrow stem cells from rats

Abstract: ObjectivesThis study aimed to assess the effect of age and osteoporosis on the proliferative and differentiating capacity of bone-marrow-derived mesenchymal stem cells (MSCs) in female rats. We also discuss the role of these factors on expression and migration of cells along the C-X-C chemokine receptor type 4 (CXCR-4) / stromal derived factor 1 (SDF-1) axis.MethodsMesenchymal stem cells were harvested from the femora of young, adult, and osteopenic Wistar rats. Cluster of differentiation (CD) marker and CXCR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
4
16
1
Order By: Relevance
“…In my study this finding may be explained by the use of the cells at passage 3 particularly as previous work has demonstrated a reduction in CD34 expression at later passage (11). The lack of difference between OVX and juvenile derived cells and CD markers, is in keeping with other work (21), that being said, the marker heterogeneity in study methodologies means only a limited inference can be made between the expression of CD markers, and the in vivo/in vitro activity of cells and as such, the value of marker expression cannot be taken in isolation. Similarly, the value of morphology is limited in isolation, though we found no difference morphologically between adipose or bone marrow derived cells, both demonstrating the same spindle like phenotype from juvenile populations, and both moved morphologically to a more flattened phenotype from aged and ovx animals.…”
Section: Discussionsupporting
confidence: 80%
“…In my study this finding may be explained by the use of the cells at passage 3 particularly as previous work has demonstrated a reduction in CD34 expression at later passage (11). The lack of difference between OVX and juvenile derived cells and CD markers, is in keeping with other work (21), that being said, the marker heterogeneity in study methodologies means only a limited inference can be made between the expression of CD markers, and the in vivo/in vitro activity of cells and as such, the value of marker expression cannot be taken in isolation. Similarly, the value of morphology is limited in isolation, though we found no difference morphologically between adipose or bone marrow derived cells, both demonstrating the same spindle like phenotype from juvenile populations, and both moved morphologically to a more flattened phenotype from aged and ovx animals.…”
Section: Discussionsupporting
confidence: 80%
“… 17 More recently, it has been shown that the development of OP is influenced by the gut microbiome. 10 Many studies 11 14 , 18 20 have also displayed the role of the gut microbiome in the pathogenesis of OP.…”
Section: Roles Of the Gut Microbiome In Osteoporosismentioning
confidence: 99%
“…Osteoporosis cause bone mineral density (BMD) loss and the degradation of the bone microstructure due to an abnormal imbalance between bone formation by osteoblasts and bone resorption by osteoclasts [ 128 , 129 ]. Additionally, MSCs population in the BM are declined with aging; thus, their function will be limited and they cannot contribute to bone formation any longer [ 130 ]. Osteoporosis is of great importance mostly because of its effect on bone fragility.…”
Section: Introductionmentioning
confidence: 99%